Analisis Komparatif Sanksi Tindak Pidana Pada Hukum Pidana Islam dengan Hukum Positif - Anwar, Reski (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2018)
Types of punishment provided for in the book the law of criminal law, namely criminal subject matter which consists of a criminal to death, imprisonment. As for the types of sanction or punishment in Islamic criminal law includes the law of jarimah adultery, penalty jarimah qadzaf, jarimah punishment of theft, jarimah punishment. Indonesia at the moment very much in need of a great variety of study on the concept of criminal sanctions in order to reduce islamic values through this Focus Group Discussion or conference, etc. Of a will can contribute to the renewal of a criminal law reform And there should have been a kind of work for punishment of the formulations in the form of social as well as the completion of matter outside the court (restorasi justice).